Production of Pigs From Porcine Embryos Generated in vitro - Chen, Paula R.; Uh, Kyungjun; Redel, Bethany K.; Reese, Emily D.; Prather, Randall S.; Lee, Kiho (Frontiers in Animal Science, 2022)
Generating porcine embryos in vitro is a critical process for creating genetically modified pigs as agricultural and biomedical models; however, these embryo technologies have been scarcely applied by the swine industry. Currently, the primary issue with in vitro-produced porcine embryos is low pregnancy rate after transfer and small litter size, which may be exasperated by micromanipulation procedures. Thus, in this review, we discuss improvements that have been made to the in vitro porcine embryo production system to increase the number of live piglets per pregnancy as well as abnormalities in the embryos and piglets that may arise from in vitro culture and manipulation techniques. Furthermore, we examine areas related to embryo production and transfer where improvements are warranted that will have direct applications for increasing pregnancy rate after transfer and the number of live born piglets per litter.